Transforming Identities in Contemporary Europe : Critical Essays on Knowledge, Inequality and Belonging. - Engebretsen, Elisabeth L. (Taylor & Francis Group, 2023)
With a focus on the Nordic region, this book explores contemporary struggles around 'identity politics' in Europe, considering various forms racist, colonialist, sexist forms of discrimination and exclusion, and the ways in which the marginalized struggle against gendered, colonial and racist legacies.